Preprints as a driver of open science: Opportunities for Southeast Asia - Irawan, Dasapta Erwin; Zahroh, Hilyatuz; Puebla, Iratxe (Frontiers in Research Metrics and Analytics, 2022)
Southeast Asia is an emerging force of open access scholarly output. For example, Indonesia is in a tight competition with Britain as the largest publisher of open access journals and the second largest producer of open access articles in the world (according to DOAJ and the COKI OA Dashboard respectively). However, this support for open practices is not yet reflected in institutional research policies in Southeast Asian countries, which still rely on criteria influenced by world university rankings that focus on publication outputs and do not incorporate elements related to research culture, integrity, or open science. Preprints have gained increasing attention across disciplines in the last few years, but they are still not included in institutional policies in SouthEast Asia. This paper discusses the potential for preprints to be a driving force for open science and for quality and integrity in scholarly outputs from Southeast Asia. There is a fledgling preprinting culture in the region, catalyzed by the RINarxiv preprint server in Indonesia and the Malaysia Open Science Platform. We argue that preprints have many advantages: opportunities for open access and for researchers to maintain copyright to their work, wide dissemination, encouraging feedback and critical thinking, and community governance. With these advantages, preprints can become a fast and open communication hub between researchers and all stakeholders in the research process. We recommend regulatory and practical steps to incorporate preprints into science policy and researchers’ practices as an effort to promote research integrity, open data and reproducibility.